The role of tawakkul as a mediator in the relationship between personality traits and depression among Muslim students in Indonesia - Fuad Nashori; Raden Rachmy Diana; Sumedi P. Nugraha; Alfian Fajar Budi Nugroho; Winda Sri Harianti; Rahmat Aziz (Psikohumaniora: Jurnal Penelitian Psikologi, 2026)
Depression is a significant mental health issue among university students, which potentially leads to academic disruption and social isolation. This quantitative cross-sectional study aims to examine the mediating role of belief in the sufficiency of God accompanied by efforts to achieve goals (tawakkul) in the relationship between personality traits and depression among Indonesian Muslim students. A total of 324 participants were recruited through a purposive sampling technique. Depression was assessed using the Depression, Anxiety, and Stress Scale, while tawakkul was measured using the Tawakkul Scale for Muslim Adults. In addition, the Big Five Personality Inventory was used to assess personality traits. Mediation analysis was employed to establish the interaction between tawakkul, personality traits and depression. The results show that tawakkul mediated the effects of neuroticism (β = .026, p = .046), agreeableness (β = –.031, p = .048), and conscientiousness (β = –.049, p = .009) on depression. Furthermore, neuroticism directly increased depression (β = .278, p < .001), whereas conscientiousness and tawakkul reduced depression (β = –.123 and –.075, p < .001). The findings emphasize the protective role of tawakkul as a faith-based coping resource that mitigates depressive symptoms among Muslim students.